Dampak sistem silvikultur intensif (SILIN) terhadap komunitas burung bawah tajuk di PT Triwira Asta Bharata, Kaltim - Adi Susilo; Indra A.S.L.P Putri (Foresty Faculty of Hasanuddin University, 2016)
The objective of the research is to identify the impact of Intensive Indonesian Selective Cutting and Replanting System (TPTII/SILIN) at dipterocarp production forest on understory birds community. Two forest blocks were compared, one with TPTII/SILIN and the other with Indonesian Selective Cutting and Replanting System (TPTI). At each forest block, 10 of 4 x 10 m mist nets were installed for three days and then they were moved to other spot for other three days. Mist nets were opened from 06:00 to 17:00 and monitored every 15 minutes. The trapped bird was identified and body size measured, then subsequently released. Data was analyzed by using Important Value Index, Shannon-Weinner Diversity Index, Margalef Species Richness Index, Simpson Dominance Index, and Sorensen Similarity Index. Number of individu, number of species, Shanon-Wiener Diversity Index were compared statistically using student t-test. The result showed that Ceyx erithacus and Arcahnotera longirostra hold the highest important value index in TPTI and TPTII/SILIN respectively. Bird abundance, Shannon-Weinner Diversity Index and Margalef Species Richness Index were lower in TPTI than TPTII/SILIN. Meanwhile Simpson Dominance Index was higher at TPTI than TPTII/SILIN. Statistical analysis for the data of the two forest blocks showed significant differences on number of individual, number of species and Shannon-Weiner Diversity Index. TPTII/SILIN was better in supporting understory birds community than those of TPTI.